BASIC SANITATION:CHALLENGES AND SOLUTIONS FOR PUBLIC MANAGEMENT (REMUNOM, 2025)
Basic sanitation is essential for promoting public health and for the sustainable development of communities. In Brazil, many municipalities face critical challenges regarding the infrastructure and management of sanitation services. This article aims to analyze the challenges faced by public management in the basic sanitation sector in São Francisco do Guaporé, identifying the obstacles, pointing out their causes and suggesting viable solutions that can be implemented in an effective and sustainable manner. The research uses a mixed methodology, with a literature review, case study and field survey with the local population and health workers. The results indicate the need for investments in infrastructure, training of managers and community engagement. It is concluded that the adoption of good management practices and the articulation between public authorities and civil society are essential to overcome the challenges identified.